From competence 1.0 to competence 4.0: An open, unifying and global education framework - Koutsopoulos, Kostis C; Kotsanis, Yannis (International Journal of Educational Technology and Learning, 2025)
This paper, in dealing with the Competence of Learning (CoL), has the purpose of substantiating that: first, the main elements of CoL—knowledge, skills, and psychosocial factors—are based on literacies, which nowadays rely on technology in the form of digital literacy; second, there have been paradigm shifts based on changes in all the major factors related to CoL; and third, these shifts have resulted in the development of four major CoL paradigms, forming a continuum from Competence 1.0 to 4.0. In addition, based on two proposed mechanisms of CoL development—the operation of triggers, fluctuations, and feedbacks, and the integration of revised taxonomies of learning objectives and outcomes—combined with the constant evolution of all the factors influencing CoL, an open, unifying, global, innovative, and comprehensive CoL framework has resulted in the form of a 3D model. The three axes of this framework are: the Domain/Content axis, which expresses individuals’ needs and enhancement in targeted subject areas and diverse academic contexts; the Competence axis, which expresses the ability to do something by learning or developing, based on knowledge, skills, and psychosocial factors; and the Integrated Scaffolding axis, which focuses on supporting learners and enabling them to progress to enhanced levels within their Zone of Proximal Development. The practical implication of this framework is that it can be utilized by/for anyone, at anytime, anywhere, for anything, satisfying the 5W1H questions of learning.